German guidelines on screening, diagnosis, and treatment of alcohol use disorders: update 2021 : guidelines - Kiefer, Falk; Batra, Anil; Petersen, Kay Uwe; Ardern, Isabel Sophie; Tananska, Daniela; Bischof, Gallus; Funke, Wilma; Lindenmeyer, Johannes; Mueller, Sebastian; Preuss, Ulrich W.; Schäfer, Martin; Thomasius, Rainer; et al. (European addiction research, 2022)
Introduction: Alcohol consumption in Germany is associated with considerable health and economic consequences. In addition to prevention, the early detection and differential treatment of those affected play an important role. The guideline “Screening, Diagnosis, and Treatment of Alcohol Use Disorders” forms the basis of this care for people suffering from alcohol use disorders. Regular updates integrate the current state of research evidence and clinical expertise. Methods: Under the auspices of the German Society for Psychiatry, Psychotherapy, Psychosomatics, and Neurology and the German Society for Addiction Research and Addiction Therapy e.V. (DG-Sucht), the 2019-2020 S3 guideline on alcohol was revised by eight working groups. Thirty-five professional societies participated in a structured consensus process to deliberate the recommendations. Potential conflicts of interest were examined in advance, documented, and taken into account during the voting on the recommendations. Results: The guideline provides recommendations on screening and brief interventions for different groups of people, as well as on treatment of individuals in the acute and post-acute phases of withdrawal. Special emphasis was placed on the treatment of comorbid somatic and psychological disorders. In addition, recommendations for specific groups of people (e.g., children and adolescents, pregnant women) have been made and adapted to the German care landscape.
Gesehen am 23.01.2024
Autoren der Guideline Group: Klaus Amann, Julia Arens, Erika Baum, Martin Beutel, Oliver Bilke-Hentsch, Gallus Bischof, Udo Bonnet, Jan Malte Bumb, Ralf Demmel, Silke Diestelkamp, Patric Driessen, Isabel Englert, Ursula Fennen, Jennis Freyer-Adam, Ulrich Frischknecht, Heribert Fleischmann, Wilma Funke, Dieter Geyer, Euphrosyne Gouzoulis-Mayfrank, Arthur Günthner, Renate Hannak-Zeltner, Barbara Hansen, Rita Hansjürgens, Ursula Havemann-Reinecke, Derik Hermann, Eva Hoch, Werner Höhl, Susann Hößelbarth, Kristin Hupfer, Bettina Jäpel, Julia Jückstock, Marianne Klein, Andreas Koch, Joachim Köhler, Michael Köhnke, Anne Koopmann, Dietmar Kramer, Oliver Kreh, Georg Kremer, Monika Krönes, Timo Krüger, Gerhard Längle, Nikolaus Lange, Bodo Lieb, Johannes Lindenmeyer, Mathias Luderer, Karl Mann, Peter Missel, Sebastian Mueller, Michael Müller-Mohnssen, Corinna Nels-Lindemann, Tim Neumann, Oliver Pogarell, Thomas Polak, Ulrich W. Preuss, Olaf Reis, Gerhard Reymann, Monika Ridinger, Hans-Jürgen Rumpf, Peter-Michael Sack, Ingo Schäfer, Martin Schäfer, Norbert Scherbaum, Welf Schroeder, Ariane Schulte, Manfred Singer, Michael Soyka, Claudia Spies, Rainer Thomasius, Natasha Thon, Clemens Veltrup, Monika Vogelgesang, Irmgard Vogt, Marc Walter, Tillmann Weber, Georg Weil, Wolfgang Weinmann, Volker Weissinger, Bernd Wessel, Tina Wessels, Arnold Wieczorek, Klaudia Winkler, Nadja Wirth, Norbert Wodarz, Dirk Wolter, Friedrich M. Wurst